Acute and Chronic Effects of Noninvasive Ventilation on Left and Right Myocardial Function in Patients with Obstructive Sleep Apnea Syndrome: A Speckle Tracking Echocardiographic Study. Issue 8 (5th April 2016) - D'Andrea, Antonello; Martone, Francesca; Liccardo, Biagio; Mazza, Mariano; Annunziata, Anna; Di Palma, Enza; Conte, Marianna; Sirignano, Cesare; D'Alto, Michele; Esposito, Nicolino; Fiorentino, Giuseppe; Russo, Maria Giovanna; et al.
Abstract : Background: In patients with obstructive sleep apnea syndrome (OSAS), repetitive hypoxia due to sleep‐induced apnea adversely affects the interaction between myocardial oxygen demand and supply, resulting in the development of subclinical cardiac dysfunction. The purpose of the study was to analyze the different involvement of left and right heart myocardial function in patients with OSAS treated with noninvasive ventilation (NIV). Methods: Conventional Doppler echocardiography, Doppler myocardial imaging (DMI), and two‐dimensional speckle tracking echocardiography (2DSTE) of left (LV) and right ventricular (RV) longitudinal and right atrial (RA) deformation were performed in 55 patients with OSAS undergoing NIV (M/F 38/17; mean age 67.8 ± 11.2 years). LV and RV global longitudinal strain (GLS) was calculated by averaging local strain along the entire right and left ventricle, before and during NIV, and after 6 months of nocturnal NIV therapy. Results: LV morphology was comparable before and during NIV, whereas LV ejection fraction and LV DMI early diastolic peak velocity were significantly improved in patients with OSAS during NIV, as was LV regional peak myocardial strain (P < 0.001). RV diameters were slightly increased in patients with OSAS during ventilation, whereas pulmonary artery systolic pressure (PASP), RV GLS, and regional peak myocardial RV strain were significantly reduced during ventilation (P < 0.0001). RA transverse diameters and RA area were also slightly increased during NIV, whereas RA lateral wall strain was reduced (P < 0.001). Acute RV myocardial impairment completely reversed at follow‐up, with a decrease in PASP and subsequent increase in both RV and RA myocardial performance. Conclusions: Conventional 2DSTE is a useful tool for assessing left and right heart morphology and myocardial deformation in patients with OSAS and for monitoring both acute and chronic effects of NIV.